Construction of induced pluripotent stem cell line (CSBZZUi002-A) from the fibroblast cells of a healthy female - Yue Wu; Xiao-Yan Meng; Hui-Fang Sun; Ying-Jie Zhang; Xiao-Hui Liu; Dian-Dian Wang; Dan-Hua Liu; Sen-Miao Li; Jia-Kang Li; Wen-Xiu Li; Shu-Ang Li; Pei-Pei Liu; et al. (Stem Cell Research)
We recruited a healthy 44-year-old female and obtained her skin fibroblasts. Subsequently, the induced pluripotent stem cell line was successfully established using non-integrated reprogramming technology. The cell line had a normal karyotype and has been confirmed to have good pluripotency through the detection of pluripotency markers and detection of teratoma formation. This cell line can serve as an effective control for studying the cellular pathological mechanisms of other specific mutations.